2017
DOI: 10.7752/jpes.2017.04302
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Abstract.Any type of activity requires learning of physical movements. However, only in physical education and sport, mastering of physical movements is the core of training, because in this case physical movement acts as an object, a means, and a goal of improvement. In sports, training has its own peculiar features, the essence of which is that the bulk of the new material is learned by mastering a variety of physical movements in the form of physical exercises. The purpose of this study was to develop a met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 3 publications
1
4
0
Order By: Relevance
“…They showed that the components of motor fitness are a priority in developing motor skills. The data presented supplement the results of studies on the peculiarities of the learning process Hakman, Nakonechniy, Moseychuk, Liasota, Palichuk, & Vaskan, 2017;Hulteen, Morgan, Barnett, Stodden, & Lubans, 2018) and the development of motor function in children (Rudd, Barnett, Farrow, Berry, Borkoles, & Polman, 2017;Kavanagh, Issartel, & Moran, 2020).…”
Section: Discussionsupporting
confidence: 71%
“…They showed that the components of motor fitness are a priority in developing motor skills. The data presented supplement the results of studies on the peculiarities of the learning process Hakman, Nakonechniy, Moseychuk, Liasota, Palichuk, & Vaskan, 2017;Hulteen, Morgan, Barnett, Stodden, & Lubans, 2018) and the development of motor function in children (Rudd, Barnett, Farrow, Berry, Borkoles, & Polman, 2017;Kavanagh, Issartel, & Moran, 2020).…”
Section: Discussionsupporting
confidence: 71%
“…Along with this, the central defenders of the motor activity associated with the implementation of jerks ahead and the preforming of the first passes for further attacking actions. Central midfielders carry out a large volume of aerobic and anaerobic motor actions when performing technical and tactical decisions on which the attacking activity of the team depends [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, physical training programming needs to pay attention to the dominant biomotor aspects of the sport. In volleyball games, the biomotor component is a fundamental physical activity that cannot be separated from physical and mental processes such as movements with various spatial structures [7]. The biomotor component is indispensable in the training process to produce professional athletes.…”
Section: Introductionmentioning
confidence: 99%